Increased Excitability of Layer 2 Cortical Pyramidal Neurons in the Supplementary Motor Cortex Underlies High Cocaine-Seeking Behaviors - Huang, Donald; Ma, Yao-Ying (Biological psychiatry (1969), 2023)
Most efforts in addiction research have focused on the involvement of the medial prefrontal cortex, including the infralimbic, prelimbic, and anterior cingulate cortical areas, in cocaine-seeking behaviors. However, no effective prevention or treatment for drug relapse is available. We focused instead on the motor cortex, including both the primary and supplementary motor areas (M1 and M2, respectively). Addiction risk was evaluated by testing cocaine seeking after intravenous self-administration (IVSA) of cocaine in Sprague Dawley rats. The causal relationship between the excitability of cortical pyramidal neurons (CPNs) in M1/M2 and addiction risk was explored by ex vivo whole-cell patch clamp recordings and in vivo pharmacological or chemogenetic manipulation. Our recordings showed that on withdrawal day 45 (WD45) after IVSA, cocaine, but not saline, increased the excitability of CPNs in the cortical superficial layers (primarily layer 2, denoted L2) but not in layer 5 (L5) in M2. Bilateral microinjection of the GABAA (gamma-aminobutyric acid A) receptor agonist muscimol to the M2 area attenuated cocaine seeking on WD45. More specifically, chemogenetic inhibition of CPN excitability in L2 of M2 (denoted M2-L2) by the DREADD (designer receptor exclusively activated by designer drugs) agonist compound 21 prevented drug seeking on WD45 after cocaine IVSA. This chemogenetic inhibition of M2-L2 CPNs had no effects on sucrose seeking. In addition, neither pharmacological nor chemogenetic inhibition manipulations altered general locomotor activity. Our results indicate that cocaine IVSA induces hyperexcitability in the motor cortex on WD45. Importantly, the increased excitability in M2, particularly in L2, could be a novel target for preventing drug relapse during withdrawal.